ANALYSIS OF THE ERUPTION PROCESS OF MOUNT MERAPI - Inelia Febriska; Dzalika HR Diyanti PA; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the basic processes of Mount Merapi's eruption through a simple simulation using readily available materials, such as baking soda, vinegar, and liquid soap. This simulation is conducted in the form of a lab experiment to help students understand how gas pressure in the